Correction: Soot and the city: Evaluating the impacts of Clean Heat policies on indoor/outdoor air quality in New York City apartments. - Carlos F Gould; Steven N Chillrud; Douglas Phillips; Matthew S Perzanowski; Diana Hernández (PLoS ONE, 2018)
[This corrects the article DOI: 10.1371/journal.pone.0199783.].